Metatranscriptomes reveal the diverse responses of Thaumarchaeota ecotypes to environmental variations in the northern slope of the South China Sea. (8th December 2022) - Lu, Ye; Lv, Yongxin; Zhang, Yu; Liu, Qian; Xu, Xuewei; Xiao, Xiang; Xu, Jun
Abstract: Thaumarchaeota are among the most abundant prokaryotes in the ocean, playing important roles in carbon and nitrogen cycling. Marine Thaumarchaeota ecotypes exhibit depth‐related diversification and seasonal changes. However, transcriptomic activities concerning niche partitioning among thaumarchaeal ecotypes remain unclear. Here, we examined the variations in the distribution and transcriptomic activity of marine Thaumarchaeota ecotypes. Three primary ecotypes were identified: a Nitrosopumilus ‐like clade; a Nitrosopelagicus ‐like water column A (WCA) clade, thriving in epipelagic water; and a water column B (WCB) clade, dominant in deep water. Depth‐related partitioning of the three ecotypes and the seasonal variability of the WCA and WCB ecotypes were observed. Nutrient concentrations, chlorophyll α and salinity were the primary environmental factors. The relative abundance of the WCA ecotype and its transcript abundance of amoA gene were positively correlated with chlorophyll α and salinity, while the WCB ecotype was positively correlated with nitrate and phosphate. Based on high‐quality metagenome‐assembled genomes, transcriptomic analysis revealed that the three ecotypes exhibited various co‐occurring expression patterns of the elemental cycling genes in the nitrogen, carbon, phosphorus, and sulfur cycles. Our results provide transcriptomic evidence of the niche differentiation of marine Thaumarchaeota ecotypes, highlighting the diverse roles of ecotypes and WCA subclades in biogeochemical cycles.